Pleuroparenchymal fibroelastosis in mycobacterium avium complex lung disease. Issue 2 (10th January 2023) - Sugino, Keishi; Ono, Hirotaka; Ando, Masahiro; Tsuboi, Eiyasu
Abstract: We report a rare case of pleuroparenchymal fibroelastosis (PPFE) with interstitial lung disease progressed after an onset of mycobacterium avium complex (MAC) lung disease. Clinicians should pay attention to the management for patients with PPFE in MAC lung disease. Abstract : We report a rare case of pleuroparenchymal fibroelastosis (PPFE) with interstitial lung disease that progressed after an onset of mycobacterium avium complex (MAC) lung disease in an 80‐year‐old Japanese woman. To our knowledge, little has been written and reported on the development of PPFE with ILD in MAC lung disease. The pathogenesis of PPFE with ILD in MAC lung disease remains obscure but it seems likely that triggers such as chronic/recurrent respiratory inflammation due to MAC infection may be involved.